2022
DOI: 10.3390/ijms23073483
|View full text |Cite
|
Sign up to set email alerts
|

High Risk-Human Papillomavirus in HNSCC: Present and Future Challenges for Epigenetic Therapies

Abstract: Head and Neck Squamous Cell Carcinoma (HNSCC) is a highly heterogeneous group of tumors characterized by an incidence of 650,000 new cases and 350,000 deaths per year worldwide and a male to female ratio of 3:1. The main risk factors are alcohol and tobacco consumption and Human Papillomavirus (HPV) infections. HNSCC cases are divided into two subgroups, the HPV-negative (HPV−) and the HPV-positive (HPV+) which have different clinicopathological and molecular profiles. However, patients are still treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 142 publications
0
13
0
Order By: Relevance
“…Unfortunately, despite previous studies suggesting an indicative role of the HPV status in the prognosis of HNSCC patients, its eligibility for guiding specific treatments is, to date, unclear ( Sun et al., 2021 ). Therefore, regardless of HPV + and HPV − HNSCC patients presenting remarkable differences in characterization, they are still provided the same therapeutic strategies ( Ghiani and Chiocca, 2022 ). Adopting a combination of surgery, chemotherapy, and radiotherapy for patients with different HPV status has resulted in unignorable side effects, as well as a tremendous economic burden to society ( Schaaij-Visser et al., 2010 ; Braakhuis et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, despite previous studies suggesting an indicative role of the HPV status in the prognosis of HNSCC patients, its eligibility for guiding specific treatments is, to date, unclear ( Sun et al., 2021 ). Therefore, regardless of HPV + and HPV − HNSCC patients presenting remarkable differences in characterization, they are still provided the same therapeutic strategies ( Ghiani and Chiocca, 2022 ). Adopting a combination of surgery, chemotherapy, and radiotherapy for patients with different HPV status has resulted in unignorable side effects, as well as a tremendous economic burden to society ( Schaaij-Visser et al., 2010 ; Braakhuis et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…One epitope predicted to have high affinity in HPV16 E7-amino acids 11-19, was not predicted to be presented in HPV33 (online supplemental figure 2E). HPV16 E7 [11][12][13][14][15][16][17][18][19] has been reported to be a critical epitope in HPV16 recognition and has been the target of several Open trials seeking to treat HPV16-driven malignancies. 21 43 44 Therefore, we infer that a deficiency in HPV E7 recognition by T cells in HPV33 HLA-A*02:01+ may pose an elevated risk of virally-driven malignancy for this HPV genotype.…”
Section: Open Accessmentioning
confidence: 99%
“… 10 While preventative vaccines provide protection against prevalent high-risk HPV genotypes, they do not appear to offer therapeutic benefit and are not projected to make a significant impact on HPV-driven malignancies for decades to come. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, HNSCC ranked as the sixth most common cancer, with 890,000 new cases and 450,000 deaths in 2018 (1), moreover, it was reported that in 2020, the number of new cases of larynx cancer was 184,615; oropharynx cancer was 98,412; and oral cavity cancer was 377,713 (2). The risk factors associated with the disease are smoking, alcohol consumption, systemic condition, socioeconomic condition, oral hygiene, viral infection with oncogenic strains [human papillomavirus (HPV) in particular HPV-16 and HPV-18], a family history of malignancy, diabetes mellitus and heavy metals found in soil (1,3).…”
Section: Introductionmentioning
confidence: 99%